2021
DOI: 10.1093/geroni/igab046.694
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Impact of Comorbid Cancer and Dementia on Health Outcomes in Older Adults: A Longitudinal Study

Abstract: Dementia and cancer are two common chronic conditions in older adults. However, there are few studies examining the prevalence of comorbid cancer and dementia and the longitudinal impact of these comorbid conditions on health outcomes. This study investigated the prevalence and longitudinal impact on health outcomes in older adults with comorbid cancer and dementia. This is a secondary analysis, using data from the 2010 and 2016 waves of the Health and Retirement Study (HRS). The health outcomes of the study i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…More than two-thirds of all new cancers are diagnosed among adults aged 60 years and older (White et al, 2019). A recent study revealed that the prevalence of comorbid cancer and dementia ranged from 2.6% to 2.8% from 2010 to 2016 in the US (Parajuli et al, 2021). Another study found that about 11%–13% of Medicare fee-for-service (FFS) patients aged 65 years and over who were hospitalized between 2013 and 2018 had co-presence of cancer and dementia (Li et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…More than two-thirds of all new cancers are diagnosed among adults aged 60 years and older (White et al, 2019). A recent study revealed that the prevalence of comorbid cancer and dementia ranged from 2.6% to 2.8% from 2010 to 2016 in the US (Parajuli et al, 2021). Another study found that about 11%–13% of Medicare fee-for-service (FFS) patients aged 65 years and over who were hospitalized between 2013 and 2018 had co-presence of cancer and dementia (Li et al, 2022).…”
Section: Introductionmentioning
confidence: 99%